2021
DOI: 10.1017/s0031182021001505
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic application of sensitive and specific phage-exposed epitopes for visceral leishmaniasis and human immunodeficiency virus coinfection

Abstract: The diagnosis of visceral leishmaniasis (VL) has improved with the search of novel antigens; however, their performance is limited when samples from VL/human immunodeficiency virus (HIV)-coinfected patients are tested. In this context, studies conducted to identify more suitable antigens to detect both VL and VL/HIC coinfection cases should be performed. In the current study, phage display was performed using serum samples from healthy subjects and VL, HIV-infected and VL/HIV-coinfected patients; aiming to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…[ 82 ], in which the cases were selected from a health service or hospital. To assess the performance of peptide-based tests, three different formats were reported: one study used an ICT format [ 7 ], two studies used phage-ELISA [ 15 , 62 ] and 19 studies used an ELISA technique [ 10 , 11 , 16 , 17 , 26 , 27 , 29 , 35 , 37 , 40 43 , 47 , 48 , 58 , 63 , 69 , 70 ]. In these studies using an ELISA method, a marked difference was observed in the amount of peptides used, which ranged from 0.25 μg to 20 μg per well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 82 ], in which the cases were selected from a health service or hospital. To assess the performance of peptide-based tests, three different formats were reported: one study used an ICT format [ 7 ], two studies used phage-ELISA [ 15 , 62 ] and 19 studies used an ELISA technique [ 10 , 11 , 16 , 17 , 26 , 27 , 29 , 35 , 37 , 40 43 , 47 , 48 , 58 , 63 , 69 , 70 ]. In these studies using an ELISA method, a marked difference was observed in the amount of peptides used, which ranged from 0.25 μg to 20 μg per well.…”
Section: Resultsmentioning
confidence: 99%
“…et al ., 2020b [ 48 ] PeptJ Molecular technique (VL patients); serology (control group) ELISA 2 μg/well II VL Brazil L. infantum Ramos F.F. et al ., 2021 [ 58 ] Pep1 Molecular technique (VL and VL/HIV-coinfeted patients), serological test (Kalazar detect Rapid test kit) (control group) ELISA 2.5 μg/well II VL Brazil L. infantum Pep2 5 μg/well Pep3 5 μg/well Pep4 2.5 μg/well Pep5 1.25 μg/well Pep6 1.25 μg/well Pep7 1.25 μg/well Pep8 2.5 μg/well Pep9 1.25 μg/well Salles, B.C.S. et al ., 2017 [ 62 ] A3 Molecular technique (VL patients); parasitology, molecular technique (TL patients) Phage-ELISA 1.00E+08 phages/well II VL Brazil L. infantum …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two selected clones were then tested in immunization protocols in BALB/c mice, and protection against L. amazonensis infection was achieved, with significant reductions in the parasite load and footpad swelling. In another study, Ramos et al (63) selected nine mimotopes using sera from VL and VL/HIV patients in the biopanning cycles. The corresponding epitopes were produced as synthetic peptides and evaluated using an ELISA against a human serological panel.…”
Section: Phage Display In Leishmaniamentioning
confidence: 99%
“…In another study, Ramos et al. ( 63 ) selected nine mimotopes using sera from VL and VL/HIV patients in the biopanning cycles. The corresponding epitopes were produced as synthetic peptides and evaluated using an ELISA against a human serological panel.…”
Section: Phage Display In Leishmaniamentioning
confidence: 99%